Advertisement Remove all ads

Express -i^-3j^+4k^ as the linear combination of the vectors 2i^+j^-4k^,2i^-j^+3k^ and 3i^+j^-2k^ - Mathematics and Statistics

Sum

Express `- hat"i" - 3hat"j" + 4hat"k"` as the linear combination of the vectors `2hat"i" + hat"j" - 4hat"k", 2hat"i" - hat"j" + 3hat"k"` and `3hat"i" + hat"j" - 2hat"k"`

Advertisement Remove all ads

Solution

Let `bar"a" = 2hat"i" + hat"j" - 4hat"k"`, 

`bar"b" = 2hat"i" - hat"j" + 3hat"k"`,

`bar"c" = 3hat"i" + hat"j" - 2hat"k"`

`bar"r" = - hat"i" - 3hat"j" + 4hat"k"`

Suppose `bar"p" = "x"bar"a" + "y"bar"b" + "z"bar"c"`.

Then, `- hat"i" - 3hat"j" + 4hat"k" = "x"(2hat"i" + hat"j" - 4hat"k") + "y"(2hat"i" - hat"j" + 3hat"k") + "z"(3hat"i" + hat"j" - 2hat"k")`

∴ `- hat"i" - 3hat"j" + 4hat"k" = (2"x" + 2"y" + 3"z")hat"i" + ("x" - "y" + "z")hat"j" + (- "4x" + "3y" - "2z")hat"k"`

By equality of vectors, we get

2x + 2y + 3z = −1

x − y + z = −3

−4x + 3y − 2z = 4

We have to solve these equations by using Cramer’s Rule.

D = `|(2,2,3),(1,-1,1),(-4,3,-2)|`

= 2(2 − 3) − 2(− 2 + 4) + 3(3 − 4)

= 2(–1) – 2(2) + 3(–1)

= −2 − 4 − 3

= −9 ≠ 0

Dx = `|(-1,2,3),(-3,-1,1),(4,3,-2)|`

= −1(2 − 3) − 2(6 − 4) + 3(− 9 + 4)

= – 1(– 1) – 2(2) + 3(– 5)

= 1 − 4 − 15

= −18

Dy = `|(2,-1,3),(1,-3,1),(-4,4,-2)|`

= 2(6 − 4) + 1(− 2 + 4) + 3(4 − 12)

= 2(2) + 1(2) + 3(– 8)

= 4 + 2 − 24

= −18

Dz = `|(2,2,-1),(1,-1,-3),(-4,3,4)|`

= 2(− 4 + 9) − 2(4 − 12) − 1(3 − 4)

= 2(5) – 2(– 8) – 1(–1)

= 10 + 16 + 1

= 27

∴ x = `"D"_"x"/"D" = (- 18)/-9 = 2`

∴ y = `"D"_"y"/"D" = (- 18)/-9 = 2`

∴ z = `"D"_"z"/"D" = 27/-9 = - 3`

∴ `bar"r" = 2bar"a" + 2bar"b" - 3bar"c"`  .......[From (i)]

Concept: Vectors and Their Types
  Is there an error in this question or solution?
Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×